Taxonomic Description and Genome Sequence of Christensenella intestinihominis sp. nov., a Novel Cholesterol-Lowering Bacterium Isolated From Human Gut - Zou, Yuanqiang; Xue, Wenbin; Lin, Xiaoqian; Hu, Tongyuan; Liu, Shao-Wei; Sun, Cheng-Hang; Luo, Guangwen; Lv, Mei; Dai, Ying; Kristiansen, Karsten; Xiao, Liang (Frontiers in Microbiology, 2021)
A Gram-staining-negative, non-spore-forming, short, straight rod, non-motile, and obligate anaerobic bacterial strain, AF73-05CM02T, was isolated from a faecal sample of a thirty-years old healthy male living in Shenzhen, China. Colonies were approximately 0.2 mm in diameter, beige and circular after 4 days of incubation on PYG agar under anaerobic conditions at 37°C. Strain AF73-05CM02T grew in a temperature range between 30-42°C and pH range from 6.0 to 8.5, with optimum growth at 37-42°C and pH 7.0. 16S rRNA gene sequence analysis demonstrated that strain AF73-05CM02T belongs to the genus Christensenella and showed the highest level of sequence similarity (98.68%) with Christensenella minuta DSM 22607T. The predominant fatty acids of strain AF73-05CM02T were C10:0 (7.5%), iso-C11:0 (5.6%), C12:0 (7.2%), C14:0 (46.6%), iso-C15:0 (7.4%), C16:0 (9.7%) and C18:1 ω9c (6.9%). Acetic acid, formic acid, butyric acid and lactic acid were the end products of glucose fermentation. The strain was negative for catalase, indole production and hydrolysis of gelatin. Genomic relatedness analyses based on average nucleotide identity (ANI) indicated that strain AF73-05CM02T significantly differed from other species of the genus Christensenella, showing ANI values less than 82.89% with the phylogenetically closest species. The G+C content of the genomic DNA was 52.07 mol% from the genome sequence, which differs from that of Christensenella minuta. Several physiological, biochemical, and genotypic properties differentiated the novel bacterial strain from the related species, indicating that the strain represents a new species of the genus Christensenella for which the name Christensenella intestinihominis sp. nov. is proposed, with strain AF73-05CM02T (=CGMCC 1.5207T =DSM 103477T) being the type strain. The follow study approached the function of cholesterol-lowering for strains AF73-05CM02T and Christensenella minuta DSM 22067T revealed the two strains exhibit capacity for removing cholesterol with efficiency of 36.6% and 54.3%. Exopolysaccharide production of two strains were 234 and 271 mg/L, respectively.